Police and the Policed: Language and Power Relations on the Margins of the Global South by Danielle Watson (2019). (8th July 2022) - Han, Zhengrui; Wu, Lihuan
Abstract : Police and the Policed: Language and Power Relations on the Margins of the Global South by Danielle Watson (2019)Palgrave Macmillan, xiii + 138 pp